Հայոց անկախ պետականության կերտման հարցի շուրջ (1918 թ. մայիս) - Պետրոսյան Գեղամ (YSU Journal of International Affairs, 2018)
After the breakup of the Transcaucasian republic, Georgia’s independence and the ultimatum imposed by the Ottoman Turkey, a very complicated and tense new military-political situation was created in the region. In fact, Armenia was completely isolated from its neighbors and remained alone against the Ottoman Turkey. Meanwhile, in mid-May 1918, Germany took serious steps to protect Georgia from military encroachments and ensure its territorial integrity, and the goal of the Tatars was not only to ensure Turkey’s influence in Transcaucasia but also to become part of the Ottoman Empire. In the current extremely difficult and tense situation, the Armenian National Council had no alternative to accept this unprecedented ultimatum (May 28) and conclude a peace treaty and save the East Armenians from new problems. On May 30, the National Council of Armenia declared itself the supreme and sole authority in the Armenian provinces, laying the foundation for the construction of a national independent statehood.